First and second pregnancy outcomes in women with class III obesity: An observational cohort study. Issue 4 (July 2021) - Wastnedge, Elizabeth A.N.; Fretwell, Janey; Johns, Emma C.; Denison, Fiona C.; Reynolds, Rebecca M.
Abstract: Introduction: Class III obesity (BMI ≥ 40 kg/m 2 ) during pregnancy predisposes mother and offspring to a range of adverse pregnancy complications and outcomes. Risk profiles vary between pregnancies and are affected by interpregnancy weight gain. We evaluated the risk of adverse outcomes in women with BMI ≥ 40 kg/m 2 in first and second pregnancies, and the impact of interpregnancy weight change on this risk. Materials and methods: Data were extracted for all women with BMI ≥ 40 kg/m 2 at first antenatal visit, who completed antenatal and delivery care for first and second pregnancies in NHS Lothian between 1/1/2009–31/12/2018. Multiple pregnancies and recipients of bariatric surgery were excluded. Results: 442 pregnancies among 221 women were included. In first pregnancy, median (interquartile range) weight was 117 kg (108.5–126.7), age 28 years (24–31) and BMI 42 kg/m 2 (41.0−44.5), 14.4% had gestational diabetes (GDM), 11.3% had pregnancy-induced hypertension and 44.6% had a post-partum haemorrhage (PPH). 20.8% of babies were large for gestational age (LGA, ≥97% centile at birth). In second pregnancy, women were heavier with a median weight of 119.9 kg (109.0−130.0, p = 0.00) with 19.9% gaining over 10 kg. Women were more likely to develop GDM (21.6%, p = 0.02). Babies were heavier with 40% of babies LGA (p < 0.0001). Interpregnancy weight change had no significant impact on GDM, pregnancy induced hypertension, PPH, perinatal mortality or LGA. Conclusions: In a population of women with BMI ≥ 40 kg/m 2, pregnancy complications are common and risk is higher in second pregnancy. The interpregnancy period is a critical time to engage women in health improvement and weight loss strategies to maximise outcomes for mother and offspring.